Protective role for properdin in progression of experimental murine atherosclerosis. - Tanja Steiner; Lorenza Francescut; Simon Byrne; Timothy Hughes; Archana Jayanthi; Irina Guschina; John Harwood; Katherine Cianflone; Cordula Stover; Sheila Francis (PLoS ONE)
Genetic, dietary and immune factors contribute to the pathogenesis of atherosclerosis in humans and mice. Complement activation is an integral part of the innate immune defence but also shapes cellular responses and influences directly triglyceride synthesis. Deficiency of Factor B of the alternative pathway (AP) of complement is beneficial in LDLR(-/-) mice fed a high fat diet. The serum glycoprotein properdin is a key positive regulator of the AP but has not been studied in experimental atherosclerosis. Atherosclerosis was assessed after feeding low fat (LFD) or high fat (HFD) Western type diets to newly generated LDLR(-/-) Properdin(KO) (LDLR(-/-)P(KO)) and LDLR-/-PWT mice. Lipids, lymphocytes and monocytes were similar among genotypes, genders and diets. Complement C3, but not C3adesarg, levels were enhanced in LDLR(-/-)P(KO) mice regardless of diet type or gender. Non-esterified fatty acids (NEFA) were decreased in male LDLR(-/-)P(KO) fed a HFD compared with controls. All mice showed significant atherosclerotic burden in aortae and at aortic roots but male LDLR(-/-) mice fed a LFD were affected to the greatest extent by the absence of properdin. The protective effect of properdin expression was overwhelmed in both genders of LDLR(-/-)mice when fed a HFD. We conclude that properdin plays an unexpectedly beneficial role in the development and progression of early atherosclerotic lesions.